The Relationship Between Indoor Air Quality And Sick Building Syndrome (Sbs) In Oil Gas Refinery - Dessy Laksyana Utami (LPPM Universitas Respati Indonesia, 2019)
The sick building syndrome comprises of various nonspecific symptoms that occur in the occupants of a building. It is commonly increases sickness absenteeism and causes a decrease in productivity of the workers. Evidence suggests that what is called the Sick Building Syndrome are at least three separate entities, which has at least one cause. The following are some of the factors that might be primarily responsible for Sick Building Syndrome such as : Chemical contaminants, Biological contaminants, Inadequate ventilation and Electromagnetic radiation. In many cases it is due to insufficient maintenance of the HVAC (heating, ventilation, air conditioning) system in the building. As this syndrome is increasingly becoming a major occupational hazard. It was used the analytic cross-sectional design. Based on data obtained 80% of respondents reported significant ongoing health problems in the eyes, head, and the nose. 60% had bad symptoms in the throat, the stomach and cough, 50% had gastrointestinal disorders, 40% fatigue and 25% occurred all symtoms sick building syndrome. The 40 respondents were recruited to the study, with a mean age of 35 years (range 20-55). To support the evidence of Sick Building Syndrome, further checks are needed for some of the factors in next research. Measurement of Chemical contaminants, Biological contaminants, Inadequate ventilation & Electromagnetic radiation. Keyword : indoor air pollution, sick building syndrome, occupational health